Moderating role of boards’ equity ownership in the relationship between corporate governance and the performance of bailed-out banks in Nigeria - Aliyu, Nuraddeen S.; Muhammad Jamil, Che Zuriana; Mohamed, Rapiah (2014)
This paper proposes the moderating role of board equity ownership in the relationship between corporate governance and performance of banks in an era of post banking crisis that called for a bailout reform.The board attributes were selected based on the peculiar problem of the banking sector, and based on the board functions that captures monitoring (agency theory based).